Colours of beauty : selecting and using Pan-Asian, Asian and Caucasian models in Singapore women's fashion magazines. - Siew, Felix. (2008)
This study seeks to better understand the selection process and apppearance of Pan-Asian, Asian and Caucasian models in advertisements and fashion spreads of local women's fashion magazines.